Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi - Mayasari Mayasari; Agung Waluyo; Wati Jumaiyah; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the factors associated with the incidence of hypertension in the Work Area of Bonegunu Health Center, North Buton Regency. This study uses a cross sectional study analytic survey design. The results of the study using the chi-square test showed that p value = 0,000 for knowledge, p value = 0.001 for physical activity / sports, p value = 0.002 for diet, p value = 0.002 infrastructure, pvalue = 0,000 for alcohol consumption, and p value = 0,000 for stress with hypertension. Conclusion, there is a relationship between knowledge, physical activity, diet, health facilities, alcohol consumption and stress with the incidence of hypertension. Keywords: Hypertension Occurrence Factors, Hypertension